2022
DOI: 10.1002/chem.202200570
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the NIR‐II Photoluminescence of Single Thiolated Au25 Nanoclusters by Selective Binding to Proteins**

Abstract: Atomically precise gold nanoclusters are a fascinating class of nanomaterials that exhibit molecule-like properties and have outstanding photoluminescence (PL). Their ultrasmall size, molecular chemistry, and biocompatibility make them extremely appealing for selective biomolecule labeling in investigations of biological mechanisms at the cellular and anatomical levels. In this work, we report a simple route to incorporate a preformed Au 25 nanocluster into a model bovine serum albumin (BSA) protein. A new app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 69 publications
0
20
1
Order By: Relevance
“…Our spectrum consists of a single band, which in the absence of KU is slightly asymmetric but upon addition of KU is well represented by a Gaussian band-shape function (Figure S4). The spectra are qualitatively different from a recently published spectrum of Au 25 ( p -MBA) 18 that displayed two distinct bands with a well-defined minimum at around 975 nm . Moreover, the authors observed that the relative intensities of the two bands changed upon changing the ligands or on association of the gold clusters with proteins.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…Our spectrum consists of a single band, which in the absence of KU is slightly asymmetric but upon addition of KU is well represented by a Gaussian band-shape function (Figure S4). The spectra are qualitatively different from a recently published spectrum of Au 25 ( p -MBA) 18 that displayed two distinct bands with a well-defined minimum at around 975 nm . Moreover, the authors observed that the relative intensities of the two bands changed upon changing the ligands or on association of the gold clusters with proteins.…”
Section: Resultscontrasting
confidence: 87%
“…The spectra are qualitatively different from a recently published spectrum of Au 25 (p-MBA) 18 that displayed two distinct bands with a welldefined minimum at around 975 nm. 28 Moreover, the authors observed that the relative intensities of the two bands changed upon changing the ligands or on association of the gold clusters with proteins. We wish to point out that the minima observed in all the reported spectra coincide with an absorption band of water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Interestingly, the PL spectrum of Au 42 in dichloromethane (DCM) shows dual emission in the NIR region (Figure B, gray profile), with peak wavelengths at 875 and 1040 nm, similar to Au 42 (BM) 32 (Figure S2B). The QY of Au 42 in DCM under ambient conditions is 11.9% (measured by an integrating sphere), which surpasses the reported thiolate-protected NCs with NIR PL ,, except Au 38 S 2 (SR) 20 (NIR QY 15%, single emission) . The PL excitation spectra for the two emissions (I and II) are similar and also track the absorption profile (Figure S3), suggesting that both emissions are associated with the HOMO–LUMO transition (Au 20 -kernel-based).…”
mentioning
confidence: 62%
“…Photoluminescence (PL) has long been of major interest in both fundamental research and practical applications, particularly, the dual emission phenomena for deciphering the underlying mechanisms and with great potentials in many fields, including ratiometric sensing, bioimaging, solar cells, and even supramolecular encryption systems. , Ultrasmall Au nanoparticles with atomic precision (1–3 nm in diameter), commonly called nanoclusters (NCs), show near-infrared (NIR) PL. The determined atomic structures and electronic structure calculations allow the elucidation of structure–property correlations, and the intrinsic merits of Au NCs such as being biocompatible, stable, and nontoxic make this class of materials quite promising for solar energy conversion and biological applications. So far, dual emission in Au NCs has only been observed in several bitetrahedral kernel structures, and the PL quantum yields (QYs) of those Au NCs in the NIR region were quite low (∼1%) …”
mentioning
confidence: 99%
“…This was due to the fact that the local environment of AuNCs attached to BSA was more constrained and prone to multiple energy transfer associated with intersystem crossing. Moreover, the capability to interact through electron-rich donor groups with the surface of the AuNCs core may increase the number of surface states involved in excitation [ 97 ]. Lately, several examples of BSA-capped AuNCs were described; for example, Dan et al described an innovative NIR-II-emitting BSA-capped AuNCs (BSA-AuNCs) with catalase-like activity for the photodynamic treatment of cancer and the healing of MRSA-infected wounds [ 98 ].…”
Section: Design and Application Of Auncs For Bioimagingmentioning
confidence: 99%